2014
DOI: 10.2478/hacq-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Management Regimes within Syntaxa of Semi-Natural Grasslands in West Bulgaria

Abstract: This study focuses on mesic and xeric grasslands of mostly secondary origin, and that are influenced by human activity. Mesic grasslands are traditionally used for hay-making, and xeric ones for pastures. Over the last 20 years, livestock farming in Bulgaria has significantly declined so that less grass is needed. Many types of grasslands are no longer used and lots of abandoned fields can be found nowadays in Bulgaria. The analyses in this study are based on 868 relevés collected on xeric and mesic grasslands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Despite their high diversity with many unique vegetation types (Tzonev et al, 2009), Bulgarian grasslands have only recently received more attention (Velev & Vassilev, 2014;Palpurina et al, 2015). However, neither diversity patterns of different taxonomic and functional vascular plant groups (but see Palpurina et al, 2015), nor diversity patterns across different spatial scales (including beta-diversity) have previously been studied in Bulgarian grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high diversity with many unique vegetation types (Tzonev et al, 2009), Bulgarian grasslands have only recently received more attention (Velev & Vassilev, 2014;Palpurina et al, 2015). However, neither diversity patterns of different taxonomic and functional vascular plant groups (but see Palpurina et al, 2015), nor diversity patterns across different spatial scales (including beta-diversity) have previously been studied in Bulgarian grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…In Slovakia, although the largest areas of abandoned grasslands are found in upland and mountainous regions, the rate of abandonment (approximately 30%-40%) is also similar in lowlands and in hilly regions. In Bulgaria, most of the abandoned permanent grasslands are located in the most distant and least accessible areas (Velev & Kirilov, 2014) and a similar situation has been observed in Romania where adverse road access and market access have had more significant effects on land abandonment than the effect of terrain (M} uller, Kuemmerle, Rusu, & Griffits, 2009 reported that considerably higher yields are likely on some types of semi-natural grassland on more fertile sites and wet meadows. In some localities therefore, the potential harvestable yield of biomass for energy production may be greater than the minimum values applied here.…”
Section: Grassland Yield Potential In Different Climatic Regionsmentioning
confidence: 59%
“…The present study has focused on Slovakia as a case study, but there are parallels with changes in other countries. Elsewhere in Eastern Europe, there have been similar institutional and economic shocks that have resulted in low profitability of ruminant livestock production (Baumann et al., ; Ruprecht, Szabó, Enyedi, & Dengler, ) and to reduced demand for grassland in agriculture (Velev & Kirilov, ). Compared with 1990, in 2013, the cattle numbers had fallen by 67%, 42%, 50% and 70% in Bulgaria, Hungary, Poland and Romania, resulting in a considerable decline in the area of cultivated and utilized grassland.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to habitat and phytocoenological studies in Bulgaria, a well-deserved place among them are the investigations of several authors [e.g., 19,20]. And these studies [21,22] add more data. There are other important studies that grab the attention for their role in Bulgaria, regarding mountain regions, their forest cover and carbon sequestration [e.g., 9,15].…”
Section: Introductionmentioning
confidence: 99%